Brand Credibility and Response Consumer on Youtuber Endorsement - Virga, Rika Lusri; Anggreni, Likha Sari; Aprianto, Yudie; Rosa, Naili (Universitas Prof. Dr. Moestopo (Beragama), 2024)
A company is developing a strategy for product introduction to a crowded audience. An effective promotional method involves endorsements by prominent figures such as celebrities and community leaders. The company utilizes its service, branded as Shipper, to deliver products. Pair Gram and a currently trending YouTuber serve as endorsers for the product. The endorsers in question are Fiki Naki and Dayana. However, disputes arose between the endorsers, leading to misunderstandings in the digital realm. This conflict resulted in many followers expressing dissatisfaction and unfollowing Dayana's account. The objective of the study is to analyze digital advertising's impact on brand credibility and consumer response to Shipper's products using ethnographic methods. The methodology involves detailed observation of social media data from Instagram, particularly the comment sections on Fiki Naki's endorsement content. The study's findings indicate that the brand credibility associated with Fiki Naki and Dayana received negative feedback from their followers in the comments. Followers perceived the endorsed products as inauthentic, viewing the videos as mere entertainment rather than genuine endorsements. The findings highlight two key concepts, consumer understanding of endorsement activities and the professionalism inherent in endorsement collaborations.